Las Redes Sociales y los Derechos Constitucionales un Estudio desde Ecuador - Cañar Torres., Ligia Magdalena (2024)
The present investigation carried out a specific analysis of the constitutional rights of honor, privacy, intimacy and freedom of expression, and their exposure and vulnerability in current digital spaces such as existing social networks; since, through their use, these rights are seriously compromised by exposing the personal data of the countless users of these digital interaction spaces. From what has been said, it has been legally argued about how the digital phenomenon constitutes a space that, although it provides the updating and academic preparation of many users, this same space describes the fragility of the data that appears in the bases of each network. Through the application of research methods such as analytical-synthetic and legal dogmatic, added to the investigative criteria outlined in this research, a plausible and commendable result has been achieved for the purpose proposed to be addressed in this study; that is, obtain valid information, based on doctrine, law and jurisprudence, that elucidates the real panorama that develops when registering and interacting on social networks, and its relationship with constitutional law. From the above, important references have been obtained that were combined with the criteria and approach of the undersigned researcher, managing to deliver a work that expresses the real circumstance that surrounds constitutional rights and social networks, when they are in harmony when using digital spaces.